The influence of local wisdom-based science learning on the cultural heritage conservation character - Mochammad Yasir; Try Hartiningsih; Annuria Auliya Rahma (Universitas Muhammadiyah Malang, 2024)
Local wisdom such as Madura bull racing and keris has uniqueness and values that are still preserved. However, there is a problem in the Gen-Z's lack of self-awareness towards the importance of local wisdom values so that there needs to be integration of local wisdom as a context with science through learning. This research aims to analyze the influence of science learning based on the local wisdom context on the cultural heritage conservation character. This true experimental research used a randomized subject control-group pre-test and post-test design with 64 science bachelor candidates. Data collected using the observation of the cultural heritage conservation character and then analyzed using the Paired Sample Test, Effect Size, N-gain, and Independent Sample Test. The results show that science learning based on the local wisdom context has proven to have an effective influence on improving the cultural heritage conservation character for bachelor science candidates. This research implies that the use of the context of local wisdom in science learning can enhance the cultural heritage conservation character as an alternative way of preserving and developing cultural and tourism heritage in the era of Sustainable Development.